Currierite, Na4Ca3MgAl4(AsO3OH)12·9H2O, a new acid arsenate with ferrinatrite-like heteropolyhedral chains from the Torrecillas mine, Iquique Province, Chile. (1st October 2017) - Kampf, Anthony; Mills, Stuart; Nash, Barbara; Dini, Maurizio; Molina Donoso, Arturo
The new mineral currierite (IMA2016-030), Na4Ca3MgAl4(AsO3OH)12·9H2O, was found at the Torrecillas mine, Iquique Province, Chile, where it occurs as a secondary alteration phase in association with anhydrite, canutite, chudobaite, halite, lavendulan, magnesiokoritnigite, quartz, scorodite and torrecillasite. Currierite occurs as hexagonal prisms, needles and hair-like fibres up to ∼200 μm long, in sprays. The crystal forms are 100 and 001. Crystals are transparent, with vitreous to silky lustre and white streak. The Mohs hardness is ∼2, tenacity is brittle, but elastic in very thin fibres, and the fracture is irregular. Crystals exhibit at least one good cleavage parallel [001]. The measured density is 3.08(2) g cm–3 and the calculated density is 3.005 g cm–3. Optically, currierite is uniaxial (–) with ω = 1.614(1) and ε = 1.613(1) (measured in white light). The mineral is slowly soluble in dilute HCl at room temperature. The empirical formula, determined from electron-microprobe analyses, is (Na3.95Al2.96Ca2.74Mg1.28Fe3+0.63Cu0.13K0.08Co0.03)∑11.80(As5+11.68Sb5+0.32)∑12(O56.96Cl0.04)∑57H30.81. Currierite is hexagonal, P622, with a = 12.2057(9), c = 9.2052(7) Å, V = 1187.7(2) Å3 and Z = 1. The eight strongest powder X-ray diffraction lines are [dobs Å(I)(hkl)]: 10.63(100)(100), 6.12(20)(110), 5.30(15)(200), 4.61(24)(002), 4.002(35)(210), 3.474(29)(202), 3.021(96)(212) and 1.5227(29)(440, 334, 612). The structure of currierite (R1 = 2.27% for 658 Fo > 4σF reflections) is based upon a heteropolyhedral chain along c in which AlO6 octahedra are triple-linked by sharing corners with AsO3OH tetrahedra. Chains are linked to one another by bonds to 8(4 + 4)-coordinated Na and 8-coordinated Ca forming a three-dimensional framework with large cavities that contain rotationally disordered Mg(H2O)6 octahedra. The chain in the structure of currierite is identical to that in kaatialaite and a geometrical isomer of that in ferrinatrite. The mineral is named in honour of Mr. Rock Henry Currier (1940–2015), American mineral dealer, collector, author and lecturer.